Chronic sleep restriction during pregnancy--repercussion on cardiovascular and renal functioning of male offspring. - Ingrid L B Lima; Aline F A C Rodrigues; Cássia T Bergamaschi; Ruy R Campos; Aparecida E Hirata; Sergio Tufik; Beatriz D P Xylaras; Bruna Visniauskas; Jair R Chagas; Guiomar N Gomes (PLoS ONE, 2014)
Changes in the maternal environment can induce fetal adaptations that result in the progression of chronic diseases in the offspring. The objective of the present study was to evaluate the effects of maternal chronic sleep restriction on blood pressure, renal function and cardiac baroreflex response on male offspring at adult age. Female 3-month-old Wistar rats were divided in two experimental groups: control (C) and chronic sleep restricted (CSR). Pregnancy was confirmed by vaginal smear. Chronic sleep restricted females were subjected to sleep restriction by the multiple platform technique for 20 h daily, between the 1st and 20th day of pregnancy. After birth, the litters were reduced to 6 rats per mother, and were designated as offspring from control (OC) and offspring from chronic sleep restricted (OCSR). Indirect blood pressure (BPi - tail cuff) was measured by plethysmography in male offspring at 3 months old. Following, the renal function and cardiac baroreflex response were analyzed. Values of BPi in OCSR were significantly higher compared to OC [OC: 127 ± 2.6 (19); OCSR: 144 ± 2.5 (17) mmHg]. The baroreflex sensitivity to the increase of blood pressure was reduced in OCSR [Slope: OC: -2.6 ± 0.15 (9); OCRS: -1.6 ± 0.13 (9)]. Hypothalamic activity of ACE2 was significantly reduced in OCSR compared to OC [OC: 97.4 ± 15 (18); OSR: 60.2 ± 3.6 (16) UAF/min/protein mg]. Renal function alteration was noticed by the increase in glomerular filtration rate (GFR) observed in OCSR [OC: 6.4 ± 0.2 (10); OCSR: 7.4 ± 0.3 (7)]. Chronic sleep restriction during pregnancy caused in the offspring hypertension, altered cardiac baroreflex response, reduced ACE-2 activity in the hypothalamus and renal alterations. Our data suggest that the reduction of sleeping time along the pregnancy is able to modify maternal homeostasis leading to functional alterations in offspring.